Coherence within and across Categories: The Dynamic Viability of Product Categories on Kickstarter - Soublière, Jean-François; Lo, Jade Y.; Rhee, Eunice Y. (Academy of Management Journal, 2024)
How does the viability of a product category shift over time? Studies abound on how categories emerge and become established, or fall out of use. Yet, extant research has often examined the evolution of categories one at a time, leaving open the question of how related categories affect a focal category’s viability. In contrast, we consider both intra- and inter-category dynamics. Viewing categories as continuously shaped by actors’ efforts to position their products, we argue that these efforts alter the coherence that products exhibit not only within a category (a category’s heterogeneity), but also across related categories (a category’s distinctiveness). We theorize how the interaction between a category’s heterogeneity and distinctiveness shapes its subsequent viability. When a focal category’s distinctiveness is low, the heterogeneity–viability relationship takes an inverted U-shape. However, as distinctiveness grows, the relationship flattens and eventually flips to a U-shape. We explain this by considering the trade-off between the “classification” and “valuation” benefits that a category affords. We find support for our argument by tracking 170 categories over an 11-year period on Kickstarter, one of the largest crowdfunding platforms. By providing a nuanced understanding of category dynamics, we shed new light onto the fluctuating viability of categories.